2001
DOI: 10.1021/jp002863k
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structure in a Shpol'skii System:  A Single-Molecule Study of Dibenzanthanthrene in n-Tetradecane

Abstract: A study is presented of the orientation of single 2.3, 8.9-dibenzanthanthrene molecules in n-tetradecane as a function of their spatial position on a length scale of 2 mm down to a few hundreds of nanometers at 1.4 K, which allows us to obtain structural information about this host/guest system. In the confocal detection volume of ∼10 µm 3 the guest molecules show two preferential orientations. A broad distribution of orientations of about (17˚is observed around these two mean orientations. The mean orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 20 publications
1
43
0
2
Order By: Relevance
“…In this case, many molecules share the same energy level, so the degree of freedom of their vibrations is drastically reduced. [183] The local environment of the molecules in the nanowires does not change in time during the emission process, and only those molecules that have energy levels corresponding to the excitation wavelength can be excited, which results in the emergence of the vibrational fine structure. Moreover, the vibrational structure became more and more resolved as the diameter decreased from 500 nm to 40 nm, which was assigned to the increase of long-range order [184] and degree of orientation [185] with decreasing wire diameter.…”
Section: Unique Luminescence From Crystalline 1d Organic Nanomaterialsmentioning
confidence: 99%
“…In this case, many molecules share the same energy level, so the degree of freedom of their vibrations is drastically reduced. [183] The local environment of the molecules in the nanowires does not change in time during the emission process, and only those molecules that have energy levels corresponding to the excitation wavelength can be excited, which results in the emergence of the vibrational fine structure. Moreover, the vibrational structure became more and more resolved as the diameter decreased from 500 nm to 40 nm, which was assigned to the increase of long-range order [184] and degree of orientation [185] with decreasing wire diameter.…”
Section: Unique Luminescence From Crystalline 1d Organic Nanomaterialsmentioning
confidence: 99%
“…However, the assignment of B to a specific DBATT site in xenon is questionable, in the context of fluorescence excitation spectra obtained for Shpol'skii matrices. For instance, in the tetradecane matrix, a "site 2" band was reported about 70 cm −1 to the blue of the main "site 1" [4]. Such similar spectroscopies in completely different hosts speak against the attribution of both bands to matrix sites.…”
Section: S-125mentioning
confidence: 99%
“…Due to the high photostability, and to the absence of spectral diffusion for DBATT embedded in naphthalene crystals, both Stark effect measurements, and interesting pump-probe experiments with strong laser fields could be performed for single molecules [2,3]. Microscopic polarization studies on DBATT in n-tetradecane revealed that guest molecules may exhibit, in a specific site of the Shpol'skii matrix, the long-range order over distances as large as approximately 2 mm [4]. This interesting result contradicts the common concept of Shpol'skii systems as highly disordered ones.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, molecules that reside in the same diffraction-limited volume element can be addressed and detected sequentially by means of high-resolution laser-induced fluorescence excitation spectroscopy. Initial measurements [11,[24][25][26] have shown that the accuracy of the lateral position determination of single chromophores reached approximately 4 nm and depends only on the signal-to-noise ratio of the fluorescence signals.…”
mentioning
confidence: 99%